TAUHID SEBAGAI PARADIGMA DALAM PENDIDIKAN ISLAM - Sugito Muzaqi; Masruroh; Indah Wahyuningsih; Ruly Ratnaningsih (Universitas Narotama, 2018)
The striking difference between the science of religion and general science makes the cause of disintegration, resulting in the dichotomy of education. First, Westerners say it is not scientific in the eyes of religion because the object is not empirical. Second, general science is sensory while the science of religion is a hallucination but the source of the Qur'an and Hadist so that the belief system is still not one hundred percent. Third, objective science in religion can not necessarily be studied by modern enthusiasts, requiring a scientific message that can assure the existence of the religious knowledge of its source from belief. To be able to collaborate between the science of religion with general science. Then, the author tries to draw the red thread that both science has a synergy if it can be practiced together, especially science of monotheism with general science. The linkage between the science can be positioned namely rahmaniyah, takamuliyah, syumuliyah, tawzuniyah, privilege, wasaliyah, rabbaniyah and uswiyah. So they understand that it can be made a tool to be united without any interests. The result of the above study then this Paradigm requires that all entities between Earth and Heaven, Empiric and Ghaib entities, are integrated in a balanced development of theory and practice of learning. Key Terms: Tawhid, General Knowledge, Paradigm, Islamic Education